Discourses on Nations and Identities - Syrovy, Daniel (XXI. Congress of the ICLA - Proceedings, 2021)
This book focuses on the interplay between concepts of nation, language, and individual as well as collective identities. Because literary communication happens within different kinds of power structures - linguistic, economic, political -, it often results in fascinating forms of hybridity. And though hybridity may be either foregrounded or regarded as compromise, it is a fascinating lens through which to look at literary history.